Overview [in Collective action and property rights for sustainable development] - Meinzen-Dick, Ruth S.; Di Gregorio, Monica (International Food Policy Research Institute, 2004)
This brief defines property rights and collective action and discusses the links to sustainability of natural resource management and agricultural systems and to poverty reduction, as well as the implications for policy and practice.